EFFECT OF LEMON AROMATHERAPY ON THE ANXIETY LEVEL OF DENTAL EXTRACTION PATIENTS IN RSND SEMARANG - Hayuratri Purwalalita Laksmidevi; Devi Farida Utami; Arinta Puspita Wati; Maria Belladonna Rahmawati (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Dental treatment that is often done is the tooth extraction procedure. The treatment and the use of sharp instruments such as syringes, pliers, bein during extraction can cause anxiety. Anxiety will be responded by several changes in the body such as the increasing of MAP, pulse rate, and respiratory rate. Handling anxiety can be done with aromatherapy, one is lemon aromatherapy.Aim: To determine the effect of lemon aromatherapy on anxiety levels and the correlation of anxiety levels with the results of MAP, pulse rate, and respiratory rate in tooth extraction patients at RSND SemarangMethod: Experimental study with pretest and posttest control group design with sampling simple random to get 40 respondents that indicated as extraction teeth patient. Respondents were divided into 2 groups: 20 control respondents and 20 intervention respondents. Anxiety level was measured by the Modified Dental Anxiety Scale (MDAS) questionnaire. Data that was not distributed normally were the difference in pulse rate and the difference in respiratory rate, while the results of the homogeneity test obtained data that were not homogeneous were the difference between the MDAS questionnaire and the difference in the MAP. The rest of the mentioned data above were all distributed normally and homogeneous. Analysis of differences in anxiety levels between before and after lemon aromatherapy was given using paired t-test, analysis of differences in anxiety levels between the control group and the intervention group using the independent t-test, and to analyzing the correlation of anxiety levels with the results of MAP, pulse rate, and respiratory rate using the Spearman test..Results: There was a significant difference in anxiety scale between before and after lemon aromatherapy was given p = 0,000135 (p <0.05) and between the control group and the intervention group p = 0.000002 (p <0.05). There was a positive correlation between anxiety levels with the results of MAP, pulse rate, and respiratory rate.Conclusion: Anxiety of tooth extraction patients shows a decreased after inhaling lemon aromatherapy. When someone is anxiety, there will be an increase in MAP, pulse rate, and respiratory rate.Keywords: Anxiety, tooth extraction, lemon aromatherapy, MAP, pulse rate, respiratory rate.